2015
DOI: 10.3390/land4030578
|View full text |Cite
|
Sign up to set email alerts
|

How to Make a Barranco: Modeling Erosion and Land-Use in Mediterranean Landscapes

Abstract: Abstract:We use the hybrid modeling laboratory of the Mediterranean Landscape Dynamics (MedLanD) Project to simulate barranco incision in eastern Spain under different scenarios of natural and human environmental change. We carry out a series of modeling experiments set in the Rio Penaguila valley of northern Alicante Province. The MedLanD Modeling Laboratory (MML) is able to realistically simulate gullying and incision in a multi-dimensional, spatially explicit virtual landscape. We first compare erosion mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 58 publications
0
22
0
Order By: Relevance
“…Some questions, though, are not easily extricated from their geographic setting. For example, models used to explore routes of hominin dispersals out of Africa (Mithen and Reed 2002) or land use in Neolithic Mediterranean contexts (Barton et al 2015) may be dependent on specific terrestrial and marine environments or spatially explicit biophysical processes. In such cases, it may be necessary to include placespecific geospatial information.…”
Section: Some Practical Considerationsmentioning
confidence: 99%
“…Some questions, though, are not easily extricated from their geographic setting. For example, models used to explore routes of hominin dispersals out of Africa (Mithen and Reed 2002) or land use in Neolithic Mediterranean contexts (Barton et al 2015) may be dependent on specific terrestrial and marine environments or spatially explicit biophysical processes. In such cases, it may be necessary to include placespecific geospatial information.…”
Section: Some Practical Considerationsmentioning
confidence: 99%
“…Naming conventions of data files indicate data type, temporality, and data permanence (intermediary data versus final data). Two versions of the MML have been developed: one where the coupler is an independent piece of wrapping software coded in Java (in MML v1; Barton et al, 2015a) and one where the coupler is integrated into the main model codebase (in Python) of a reduced version of MML (in MML-Lite; Barton et al, 2015b). Subcomponent models are also either independent software scripts coded in Python (Landscape components) or in Java (ABM) in the MML v1 or are coded in a monolithic Python codebase in the MML-Lite.…”
Section: Feedback Implementationmentioning
confidence: 99%
“…Surface-process models (sometimes combined with agentbased models) have suggested that in semiarid areas with significant topographic relief, even limited settlement by Neolithic farmers or pastoralists can have outsized impacts on local and downstream dynamics of intermittent watercourses, initiating arroyo/barranco formation that reduced agricultural productivity by eroding fields in some areas and burying them in others (86). These processes can happen even without climate change, although they can be exacerbated by climate change.…”
Section: Climate and The Spread Of Farming In Asiamentioning
confidence: 99%